اثر تطبيق التدقيق وفق معايير التدقيق الدولية في تحسين جودة المعلومة المالية في المؤسسات البنكية -دراسة لمجموعة من البنوك في الجزائر- - بن الدين, امحمد; عوماري, عائشة; عوماري, فاطمة (Université de M'sila, 2017)
This study aims to identify the impact of the application of banking auditing according to international auditing standards on improving the quality of financial information in the Algerian banks. In order to achieve the objectives of the study a questionnaire was used targeting officials and employees of public commercial banks in Algeria through their agencies in Adrar province. The Statistical Package for Social Sciences (SPSS) was used to analyze questionnaire data, and to test hypotheses, And the study found a positive relationship between the role of the external auditor and the quality of financial information; in addition it showed a relatively strong relationship between the external auditor's report and the quality of the financial information according to the sample being investigated. The study recommends elevating the level of disclosure in banking institutions and boosting awareness among officials about the positive role of the auditor in raising the level of trust in the institution's information for stakeholders With necessity to Emphasis on compliance with international auditing standards by external auditors, and their commitment to the limits of their relationship with supervisors of activities within banks and their commitment to the limits of their relationship with supervisors of activities within banks.
Keywords: Auditing, International Auditing Standards, Banking Institutions, Financial Information, Quality of Financial Information.